Examining and analysing the determinants of non-performing assets in public and private sector banks in India. (6th March 2023) - Singh, Swati; Arora, Manpreet
There is no doubt that the Indian financial sector is growing at an efficient rate but at the same time the growth rate of non-performing assets (NPAs) of the banks are also increasing. There is a high variation of growth of these NPAs among different groups of banks. This paper examines the effect of various important variables on net NPAs. Panel data regression is used for analysing the data. For the analysis purpose, dataset of 20 public sector banks and 18 private sector banks from year 2009-2019 is considered. Data is collected from various reports of RBI. GMM model is applied to solve the problem of endogeneity. Results and analysis showed that capital adequacy tier I, net interest margin, burden ratio and bank size have negative and significant effect on NPA, whereas intermediation cost showed positive and significant effect on NPA.